Self-Assessment in Islamic Education: Its Effectiveness on Speaking Performance at Madrasah Aliyah Al-Khoirot Malang - Mohammad Fiqri Fahriza Aswali; Budik Kusworo (Lembaga Pengembangan Kinerja Dosen, 2025)
This quasi-experimental study investigates the effectiveness of self-assessment in the context of Islamic education, specifically focusing on its impact on students’ English speaking performance at Madrasah Aliyah Al-Khoirot Malang. The research adopts a pre-test and post-test control group design to measure students' development in speaking skills. A total of 40 secondary-level students participated, divided equally into experimental and control groups. The experimental group received instruction that incorporated self-assessment strategies, while the control group was taught using conventional methods without self-assessment integration. Data collection was conducted through structured speaking assessments administered before and after the intervention. The results demonstrated a notable improvement in the experimental group's speaking performance, with their mean score increasing from 57.65 (pre-test) to 63.90 (post-test). In contrast, the control group exhibited only a slight increase from 54.70 to 55.80. Statistical analysis using SPSS version 25 and a significance level of α = 0.05 revealed a p-value of 0.039, which is less than 0.05, indicating a statistically significant difference between the two groups. These results confirm that self-assessment positively influences students' speaking proficiency. Beyond score improvements, students in the experimental group also showed increased self-awareness, better self-regulation, and deeper reflection on their speaking abilities, identifying their strengths and areas for improvement more effectively. This suggests that self-assessment fosters not only language performance but also metacognitive skills that are crucial for lifelong learning. This study contributes to the relatively limited body of research on self-assessment practices in Islamic education environments, particularly within madrasah contexts. It highlights the pedagogical value of self-assessment in enhancing speaking skills and suggests that incorporating self-reflective practices in language instruction can lead to more autonomous and engaged learners.